Sebastián Piñera represented at president Gabriel Boric’seulogy - Vásquez Leyton, Juan Francisco (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
This article analyzes the representation of late former Chilean president Sebastián Piñera in President Gabriel Boric’s eulogy speech during his state funeral. Using both Jäger’s Critical Discourse Analysis, and framing theory, the article examines how, following the former president’s death, Boric emphasized his democratic legacy and leadership in public life over political disagreements. The speech also displays calls for unity and symbolisms that reinforce Boric’s republican values. The analysis concludes that this speech not only reconfigures Piñera’s image, but also strengthens the president’s own discursive strategy in a context of political friction.
Keywords: Presidential speech; Representation; Political leadership; Sebastián Piñera; Gabriel Boric